Tamtsil Al Marah Fi Majmuati Qashaid “Anta-Lii” Li Nizar Qabaani Bi Nadzariyah Michael Riffatere - Soni Fauzi; Dzun Nur Nafi’ah Muamaroh; Arief Rahman Hakim; Khafid Roziki (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This research aims to know the indicative reading, the hermeneutic reading, and the indirect expression of the representation of women in the collection of poems